2006
DOI: 10.1108/09526860610661473
|View full text |Cite
|
Sign up to set email alerts
|

Six Sigma arises from the ashes of TQM with a twist

Abstract: On each project, intense study is used to determine root cause analysis; and in the end, a metric known as "sigma level" can be assigned to signify the level of quality. Six Sigma has a "critical to quality" dimension that keeps the quality effort focused on improving only those things that really matter to the customer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 9 publications
1
66
0
1
Order By: Relevance
“…Furthermore, literature has highlighted one of TQM's shortfalls being the inability to remove recognised root causes, thus causing organisations to revert back to their original performance due improvement gains being lost over time (Black and Revere, 2006). In addition, DahlgaardPark (2011) identified that negative criticism of TQM comes in two forms: the lack of consensus about the true definition of TQM, and the way in which some organisations have failed to implement the approach correctly.…”
Section: Tqm: Is It Still Alive?mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, literature has highlighted one of TQM's shortfalls being the inability to remove recognised root causes, thus causing organisations to revert back to their original performance due improvement gains being lost over time (Black and Revere, 2006). In addition, DahlgaardPark (2011) identified that negative criticism of TQM comes in two forms: the lack of consensus about the true definition of TQM, and the way in which some organisations have failed to implement the approach correctly.…”
Section: Tqm: Is It Still Alive?mentioning
confidence: 99%
“…In the current situation of high global competition and a climate of cost reductions, Six Sigma achieves significantly more on areas (Grima et al, 2013), "where some existing TQM efforts In addition, it is believed that Six Sigma has risen from the ashes of TQM and its shortages by introducing new concepts and approaches (Black and Revere, 2006); with literature suggesting that Six Sigma application of root-cause techniques discovers variability, and ensures a more thorough search than any other previous quality improvement. Perhaps due to Six Sigma being data-driven, using measurements to analyse problems and thereby improve the process or outcome, and enabling organisations to position their quality improvement effort in comparison to others (Grima et al, 2013); all of which can be compared to TQM, which has no way to measure quality (Black and Revere, 2006).…”
Section: Six Sigma: a Replacement For Tqm?mentioning
confidence: 99%
See 1 more Smart Citation
“…The SS as a well-structured continuous improvement methodology to reduce process variability and remove waste within the business processes [6][7][8]. It is defined as a set of statistical tools adopted within the quality management to construct a framework for process improvement [9]. It is also as an operational philosophy of management which can be shared beneficially by customers, shareholders, employees and suppliers [10,11].…”
Section: Six Sigma (Ss)mentioning
confidence: 99%
“…This is because it is an essential element of Six Sigma, which has been extensively implemented in industry (Black and Revere, 2006;Antony, 2004) and lean Six Sigma, which has also received considerable attention from academics, researchers and industrialists (George et al, 2005;Näslund, 2008).…”
Section: Literature Review On Six Sigma and Dmaicmentioning
confidence: 99%